Physicochemical Quality and Sensory Acceptance of Jerusalem Artichoke (Helianthus tuberosus L.) Flower Tea - ฤทธิเลิศ, ภาสุรี (Thai Journal of Science and Technology, 2021)
The purpose of this study was to analyze the total polyphenol content and antioxidant activity of Jerusalem artichoke flower tea and the consumer acceptance of Jerusalem artichoke flower tea infusions. The result showed that Jerusalem artichoke flower tea gave the yellow-red color. The total polyphenol content and antioxidant activities determined by 2,2-diphenyl-l-picrylhydrazyl (DPPH) assay of Jerusalem Artichoke flower tea was 25.13±1.41 mg eq GA/g of dry weight and 63.44±2.97 mmole TE/g of dry weight, respectively. For consumer acceptance, The tea infusion which was used Jerusalem artichoke flower tea at 1.50 g received the highest appearances, odor, flavor, aftertaste, and overall acceptance score was like slightly (p≤0.05). Conclusively, Jerusalem artichoke flower tea effectively shows antioxidant property which is suitable to develop formula as a tea product for health care.